A Metode Analisis Interaksi Tanah Struktur yang Diusulkan dengan Pertimbangan Respon Elastis Tanah: Metode Analisis Interaksi Tanah Struktur yang Diusulkan dengan Pertimbangan Respon Elastis Tanah - Priyono, Pujo; Alihudien, Arief (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
The soil structure-interaction analysis method is a structural analysis method in which the structure and foundation are treated as a complete structural system. Until now, the concept of analysis was that soil was idealized as a set of springs that had a unit value of foundation modulus obtained from the assumption that the ground contact stress was linear (evenly distributed). The fact is that for relatively rigid structural systems, ground contract tension is not linear. This study aims to examine whether there is a difference in the internal forces on structural element elements as a result of the analysis of structure-soil interaction assuming this ground contact stress (evenly distributed), when compared with the results of the ground-structure interaction analysis by taking into account the inlinearity of the contact stress. Research using computer aids and computer programs (SAP2000). Examples of structures were chosen that were symmetrical with the load distribution altered in such a way as to obtain values of ratios between the vertical reaction at the outermost pedestal (Rt) and the vertical reaction at the innermost pedestal (Rd) of 0.6, 0.5 and 0.4. The soil condition chosen is a type of clay soil with two kinds of conditions, namely soft and medium tanaah. The results show that whether the soil conditions are soft or moderate, most moments in an element image make a significant difference to all Rt/Rd values.